2015
DOI: 10.1016/j.leaqua.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Getting it done and getting it right: Leader disciplinary reactions to Followers’ moral transgressions are determined by construal level mindset

Abstract: All normative leadership theories suggest that disciplining followers that transgress moral norms is a crucial leadership task. However, leaders sometimes yet fail to do so. Previous research has indicated that leaders may refrain from enacting discipline out of self-interest or from concern for the organization's interest. We explore another option: leaders may simply be unwilling to enforce moral norms because of a negative attitude towards them. We argue and show that leaders that construe norms on relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 88 publications
1
23
0
Order By: Relevance
“…Second, by relying on construal level theory to explore the antecedents of vision communication, we add to the emerging but scarce literature that has started to apply the insights of construal level theory to the study of leadership (Berson et al, 2015;Berson & Halevy, 2014;Popper, 2013;van Houwelingen et al, 2015). In line with these studies, our results echo a similar message that insights from construal level theory can indeed be used to enhance our understanding of leadership phenomena.…”
Section: Theoretical Implicationssupporting
confidence: 72%
See 1 more Smart Citation
“…Second, by relying on construal level theory to explore the antecedents of vision communication, we add to the emerging but scarce literature that has started to apply the insights of construal level theory to the study of leadership (Berson et al, 2015;Berson & Halevy, 2014;Popper, 2013;van Houwelingen et al, 2015). In line with these studies, our results echo a similar message that insights from construal level theory can indeed be used to enhance our understanding of leadership phenomena.…”
Section: Theoretical Implicationssupporting
confidence: 72%
“…For instance, Popper (2013) used construal level theory to explain how leader perceptions are a function of psychological distance, and Berson et al (2015) proposed that follower motivation is a function of the match between the construal level of leader message attributes and situational attributes. In terms of empirical research, van Houwelingen, van Dijke, and De Cremer (2015) showed that construal level influences leaders’ decision to discipline followers after transgression of moral norms. Demonstrating the importance of a match between the situation and leader communication in terms of construal level, van Houwelingen, Stam, and Giessner (2017) found that leader appeals to desirability (feasibility) were more effective when the spatial distance between leaders and followers was high (low).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Out of these, 13 studies showed empirical evidence that representing objects or events as high-level construals or as psychologically distant is directly associated with stronger moral judgments and increased moral behavior (Agerström & Björklund, 2009a, 2009bAgerström, Björklund, & Carlsson, 2012Choi, Park, & Oh, 2012;Eyal et al, 2008;Napier & Luguri, 2013;Nordhall & Agerström, 2013;Rixom & Mishra, 2014;Tumasjan, Strobel, & Welpe, 2011;van Houwelingen, van Dijke, & de Cremer, 2015;Yi, Charlton, Porter, Carter, & Bickel, 2011). Two studies showed opposing results such that low-level construals and psychological proximity elicited stronger moral judgment and increased moral behavior (Gong & Medin, 2012;Lammers, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, some of the methods used to induce different levels of construal have been to manipulate participants' focus on (a) the 'why' versus 'how' of certain events (e.g., Gong & Medin, 2012;Luguri et al, 2012;Napier & Luguri, 2013;Rixom & Mishra, 2014;van Houwelingen et al, 2015), (b) the superordinate versus subordinate features of certain objects (e.g., Gong & Medin, 2012;Luguri et al, 2012;van Houwelingen et al, 2015), or (c) the big picture versus immediate consequences of the moral dilemmas (e.g., Lammers, 2012). Arguably, indications that different kinds of manipulations of construal level lead to the same outcome adds to the construct validity of construal level.…”
Section: Methodsological Limitationsmentioning
confidence: 99%
“…Participants were informed that over the course of the study, they would be working for a small simulated company consisting of one CEO, several middle managers, and a number of low‐level subordinates (adapted from Van Houwelingen, Van Dijke, & De Cremer, ). Each middle manager was responsible for two subordinates and reported to the CEO.…”
Section: Methodsmentioning
confidence: 99%